Solution:
We are going to find the first derivative of a function "Y= x* x^{\\frac 1 2} + \\frac 2 {x^{2}}"
We have a formula, Derivative of "x^{n} =" "n * x^{n-1}"
First we can rewrite the given function as Y = "x^{ 1 + \\frac 1 2} + \\frac 2 {x^2}" = "x^{\\frac 3 2} + 2 * x^{-2}"
since, in the multiplication, If the bases are equal , we can add the power)
( If we have a term with positive exponent at the denominator, we write that at numerator with negative exponent)
Now, the derivative of the given function
Derivative of "Y = \\frac 3 2 * x^{ \\frac 3 2 - 1} + 2 (-2) * x^{ - 2 -1}"
= "\\frac 3 2 * x^{\\frac 1 2} - 4 * x^{ -3}"
Answer: Derivative of Y ="\\frac 3 2 * x^{\\frac 1 2} - \\frac 4 {x^{3}}"
Comments
Leave a comment